(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
This study aimed at evaluating the antidiarrhoeal effects of methanolic root extract of Detarium microcarpum. The root of Detarium microcarpum was collected air-dried, ground to powder and extracted with methanol by cold extraction method to give a percentage yield of 9.65% w/w. The antidiarrhoeal effect of the methanol root extract on castor oil-induced diarrhoea, intestinal charcoal meal transit and castor oil-induced enteropooling were determined. The root extract of Detarium microcarpum produced a significant dose-dependent protection (p<0.05) against the castor oil-induced diarrhoea with the highest protection of 76.7% obtained at the highest dose tested (400mg/kg). The extract showed a significant intestinal charcoal meal transit (p<0.05) as it had 45.5%, 53.8%, and 62.4% inhibition respectively when compared to distilled water, the negative control (0% inhibition). Atropine however produced a significant increase (p<0.05) in intestinal charcoal meal transit at 78.1% inhibition. There were no significant differences (p>0.05) between the extract doses 100, 200, 400 mg/kg administered. The methanol extract at 100, 200, and 400 mg/kg showed 25.4%, 40.7% and 78.8% fluid accumulation respectively. The positive control Atropine (5 mg/kg) had 82.3% inhibition of intestinal content when compared to the negative control (distilled water treated rats) which had 0% inhibition. The results obtained from this study revealed that the root extract of Detarium microcarpum possesses antidiarrhoeal effect. The plant extract is recommended for bioassay-guided isolation and characterization of the active compounds responsible for the antidiarrhoeal property.